A new genetic lineage of Asparagopsis taxiformis (Rhodophyta) in the Mediterranean Sea: As the DNA barcoding indicates a recent Lessepsian introduction - Omri Nahor; Tal Luzzatto-Knaan; Álvaro Israel (Frontiers in Marine Science, 2022)
Asparagopsis taxiformis (Delile) Trevisan is a red marine macroalga (Bonnemaisoniales, Rhodophyta) with high invasive potential and broad worldwide distribution. In the Mediterranean Sea, A. taxiformis was reported before the opening of the Suez Canal and is comprised of two different cryptic lineages, named L2 and L3. As for the Israeli Mediterranean Sea (IMS), A. taxiformis benthic populations have seemingly expanded with several large seasonal blooms recorded in recent years. However, neither ecology nor molecular substantial studies have been conducted for this particular geographical area. Increasing sampling intensity and geographical coverage may reveal new lineages or indicate human-mediated spread routes not only for A. taxiformis but for macroalgae in general. This approach is particularly important in areas such as the eastern Mediterranean Sea, which experiences intense biological invasion on a global scale. In this study, randomly samples specimens (n = 30) of A. taxiformis and preserved herbarium samples (n = 4) collected from the IMS in the past, were all barcoded and taxonomically identified using three molecular genetic markers (LSU, cox 2-3 spacer, and rbc L). We found a cryptic lineage 4 (L4) of A. taxiformis first reported here for the Mediterranean Sea, and previously described for the western Indo-Pacific and Hawaii. Herbarium samples confirmed the presence of L4 as early as 2013. Comparative assessment of cox 2-3 spacer marker indicates 100% similarity to sequenced L4 samples from Egypt in the Red Sea. The IMS cox 2-3 spacer sequences differed from previously sequenced samples from the Mediterranean Sea by 2.3% and 3.9% bp, compared to L3 and L2 Mediterranean populations, respectively. Morphological inspections indicate monoecious L4 gametophytes which are larger than the L4 population reported previously from Hawaii. Altogether, our results strongly indicate a Lessepsian migration route for A. taxiformis L4 with yet unknown consequences for the local marine ecosystems.

Differential pathogenicity and genetic diversity among Pectobacterium carotovorum ssp. carotovorum isolates from monocot and dicot hosts support early genomic divergence within this taxon - Moran Yishay; Saul Burdman; Angel Valverde; Tal Luzzatto; Ron Ophir; Iris Yedidia (Environmental Microbiology, 2008)
Summary The capability of Pectobacterium carotovorum isolates to infect monocotyledonous plants has been previously reported; however, no full consideration was given to characterize the association between such isolates and their monocot hosts. To assess differences in aggressiveness among P. carotovorum ssp. carotovorum isolates originating from monocotyledonous or dicotyledonous plants, we used as model plants two susceptible monocot hosts, the ornamentals Zantedeschia aethiopica and Ornithogalum dubium , as well as two common dicot hosts, Solanum tuberosum and Brassica oleracea . Using virulence assays and different genetic analyses we characterized P. carotovorum ssp. carotovorum isolates from diverse geographical locations which originated from plants belonging to four unrelated orders of monocots and five orders of dicots. Invariably, isolates originating from monocots exhibited higher virulence towards the tested monocot plants than dicot isolates, independently of their geographical source. Moreover, monocot and dicot isolates were clearly differentiated by various genetic analyses, such as 16S rRNA sequence clustering, intergenic transcribed spacer‐PCR (ITS‐PCR) banding pattern and amplified fragment length polymorphism (AFLP). We propose that the observed relationship between pathogenicity and genetic diversity among P. carotovorum ssp. carotovorum isolates reveals a co‐evolutionary specialization trend in the interaction between this pathogen and its hosts.